Traços da culpa: estudo comparativo e gendrado da repressão feminina em Lucíola, de José de Alencar - Sousa, Maria da Glória Ferreira de (2016)
There are several means by which repression against female sex, so pungent in many moments of human trajectory, is demonstrated in literature, being the guilty conscience one of the oldest ways these representations take and perhaps the most tragical. Admitting the importance of this feeling as the main basis for delineation of Lúcia’s story, from José de Alencar’s novel, Lucíola, this work aims to answer how the social and cultural factors, specially gender inequalities and their consequent dual morality standard, are articulated so that it results in the protagonist’s repression by herself. It is divided in four chapters. The first intends to verify how some of the historical female domination processes took their forms, including there symbolic domination that sees guilty as one of its most effective instruments. Also, some psychosocial aspects of this feeling and how it transfigures in prostitute’s stigmatization promoted by themselves will be analysed. In the second chapter, Romanticism is focused. It examines the importance of this movement in the crystallization of patterns that limited even more female sex as well as the place José de Alencar holds in this context with his singular protagonists – these ones formed with dense psychological bagagge. In the third chapter, the analysis of Lúcia’s sense of guilt take shape with specific attention to Christianity’s blaming methods and their assimilation by Maria da Glória. The fourth chapter, finally, reveals the way Maria’s sense of guilt results in Lúcia’s conception and, from a psychoanalytic and gendered perspective, studies the mechanisms involved in the development of this feeling, just like its consequences, all this ruled by observations of nineteenth century woman’s idealization that contributed to sinuosities of relation female/guilt. To the accomplishment of these studies some authors were essencial, like Pierre Bourdieu (2014), Thomas Bonnicci (2007), Jonathan Culler (1999), François Furet (1999), Heinrich Heine (1991), Antônio Cândido (2006), but mainly, Freud (2011), Nietzsche (2009) and theorizations of Alencar himself, always having in mind a better contribution to the studies of different roles both sexes represent in literature and the processes of symbolic domination that have as their goal the achievement of these gaps – namely the process of guilt internalization.